The Influence of Promotion on TikTok Live Streaming Selling on Consumer Purchasing Decisions in Take on Thrift Online Businesses - Veronika, Veronika; Indriati, Ellen (Dinasti Publisher, 2025)
This study aims to determine the effect of promotion through TikTok live streaming selling on consumer purchase decisions in the online business Take on Thrift. The research uses a quantitative approach with an explanatory method, and data collection was conducted through online questionnaires distributed to consumers who had watched and purchased products from Take on Thrift’s live streaming sessions. The total number of respondents in this study was 100, selected using purposive sampling. The analysis results showed that all questionnaire items were valid and reliable. A simple linear regression test indicated that the promotion variable has a positive and significant influence on purchase decisions, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.906, meaning that 90.6% of the variation in purchase decisions can be explained by promotion through TikTok live streaming selling. These findings demonstrate that interactive promotions carried out through TikTok live streaming selling can significantly influence consumer purchase decisions.